2001
DOI: 10.1007/s00268-001-0047-y
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical carcinomas: surgical trends and results of a 253‐patient series from the French Association of Endocrine Surgeons study group

Abstract: Because of the rarity of adrenocortical carcinoma, survival rates and the prognosis for patients who have undergone operation are not well known. The purpose of the French Association of Endocrine Surgery was to evaluate these factors over an 18-year period. A trend study was associated to assess changes in the clinical and biochemical presentations as well as the surgical evolution. A total of 253 patients (158 women, 95 men) with a mean age of 47 years were included. Cushing syndrome was the main clinical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
435
6
28

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 495 publications
(493 citation statements)
references
References 30 publications
19
435
6
28
Order By: Relevance
“…[3][4][5][6][7] Mitotane is the only drug approved for the treatment of adrenocortical carcinoma and is used both as adjuvant therapy and for advanced disease, [8][9][10][11][12][13][14] although its efficacy has never been shown in a randomized trial. The experience with other antineoplastic drugs for the treatment of this disease is even more limited.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] Mitotane is the only drug approved for the treatment of adrenocortical carcinoma and is used both as adjuvant therapy and for advanced disease, [8][9][10][11][12][13][14] although its efficacy has never been shown in a randomized trial. The experience with other antineoplastic drugs for the treatment of this disease is even more limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, other investigators have reported similar staging of disease at diagnosis and survival rates between incidentally discovered adrenocortical carcinomas and non-incidental carcinomas (111 -114). Indeed, the incidental identification of asymptomatic adrenocortical incidentalomas seems to have led to only a very modest reduction in the number of patients who present with metastatic disease (113,115).…”
Section: Incidentally Discovered Adrenocortical Carcinomamentioning
confidence: 99%
“…ACC is a highly aggressive tumor with poor prognosis and an overall survival rate of 5 years of 25-50% in most series [1,2,3,4,5,6]. The rarity of ACCs is a major limitation to our understanding of their pathophysiology.…”
Section: Introductionmentioning
confidence: 99%